2000
DOI: 10.1021/la0002278
|View full text |Cite
|
Sign up to set email alerts
|

Micelles, Dispersions, and Liquid Crystals in the Catanionic Mixture Bile Salt−Double-Chained Surfactant. The Bile Salt-Rich Area

Abstract: The phase behavior and phase structure for the catanionic pair sodium taurodeoxycholate-didodecyldimethylammonium bromide (DDAB) are investigated, at 25°C. A combination of techniques is used including light and electron microscopy, small-angle X-ray scattering, and pulsed field gradient NMR self-diffusion. The bile salt micellar solution incorporates large amounts of the double-chained amphiphile, with the solution region extending to equimolarity. On the contrary, the hexagonal liquid-crystalline phase is de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 57 publications
1
41
0
Order By: Relevance
“…The system containing sodium taurodeoxycholate and a double chain surfactant, DDAB (didodecyldimethylammonium bromide) was also presented [110]. The latter system is especially interesting, since DDAB is used in mixture with lipids and imparts a positive charge to the resulting vesicles [111]. In that system a wide solution region extends from the BS-rich side up to the DDAB-rich one.…”
Section: Ternary Systemsmentioning
confidence: 99%
“…The system containing sodium taurodeoxycholate and a double chain surfactant, DDAB (didodecyldimethylammonium bromide) was also presented [110]. The latter system is especially interesting, since DDAB is used in mixture with lipids and imparts a positive charge to the resulting vesicles [111]. In that system a wide solution region extends from the BS-rich side up to the DDAB-rich one.…”
Section: Ternary Systemsmentioning
confidence: 99%
“…Vitrified samples were prepared, transferred and imaged according to the usual procedure, described in previous works [24,25,37]. A Philips CM120 Bio-Twin microscope was used, especially designed for handling cryogenic samples.…”
Section: Cryogenic Transmission Electron Microscopymentioning
confidence: 99%
“…Both the phospholipid and DDAB are vesicle-and lamellarforming amphiphiles; however, the presence of the headgroup electrostatic interactions and salt (NaBr) in the catanionic system brings a new complexity to the phase equilibria and aggregation processes. Previously, the phase behavior and aggregation phenomena were studied for the same catanionic pair, in the bile salt rich area [37]. It was reported that the system displays coacervation instead of precipitation at equimolarity, consisting of a viscous isotropic solution in equilibrium with a very dilute solution.…”
mentioning
confidence: 99%
“…It becomes by far more extended in the case of DDAB-STDC-D 2 O [1]. Noteworthily, detailed rheological and NMR diffusivity measurements enlightened a dramatic microstructural change occurring at the equimolar line, from dis- crete to branched, interconnected micelles [4].…”
Section: Introductionmentioning
confidence: 99%
“…The association of the two surfactants didodecyldimethylammoniun bromide (DDAB) and sodium taurodeoxycholate (STDC), which differ under various respects beside charge, gives rise to a variety of intriguing self-assembly motifs, as revealed by Marques et al [1][2][3][4]. STDC is a bile salt (Fig.…”
Section: Introductionmentioning
confidence: 99%